Twisted fallopian tube in pregnancy: a case report - Intharasakda Praguypruek; Phupong Vorapong (BMC, 2001)
Abstract Background Isolated twisted fallopian tube is an uncommon event, isolated twisted fallopian tube in pregnancy is also very rare. The diagnosis is often difficult and established during the operation. The right fallopian tube is most common affected. Case presentation We report an uncommon twisted left fallopian tube in pregnancy. A 34-year-old G3P2 28 weeks pregnant woman presented with acute left lower abdominal pain. The clinical and ultrasonographic findings led to diagnosis of twisted left ovarian cyst. Emergency exploratory laparotomy was performed. A twisted left fallopian tube and paratubal cyst was noted and left salpingectomy was performed. The postoperative course was uneventful and the pregnancy continued until term without complication. Conclusions Although isolated twisted fallopian tube during pregnancy is very rare, it should be included in the differential diagnosis of acute abdomen in pregnancy. Early surgical intervention will decrease obstetric morbidity and may allow preservation of the fallopian tube.